Xylogenesis under future climates: enhanced growth of balsam fir in a warming boreal forest - He, Minhui; Sylvain, Jean-Daniel; Silvestro, Roberto; Drolet, Guillaume; Arsenault, Richard; Rossi, Sergio (Frontiers in Plant Science, 2025)
Understanding the effects of climate variability on tree growth is crucial to predict forest carbon sequestration under global climate change. This study investigates the dynamics of wood formation in balsam fir in response to historical climatic data and projected variations. Weekly microcores were collected from 33 permanent plots in a boreal forest in Québec, Canada, over five growing seasons from 2018 to 2022. Warmer spring temperatures were associated with earlier cell enlargement initiation and increased cell production, whereas precipitation exerted a limited effect. An advancement in the onset of cell enlargement by 14–42 days and a 25–85% increase in cell production from 2051–2080 relative to the reference period (1981–2010) were predicted. Our results reveal potential shifts in growth dynamics and xylem production that could modify the growth processes in balsam fir, including carbon sequestration in the boreal forest ecosystems of Eastern Canada.